Results from the CUORE-0 experiment. Issue 6 (May 2016) - Canonica, L; Alduino, C; Alfonso, K; Artusa, D R; Avignone III, F T; Azzolini, O; Banks, T I; Bari, G; Beeman, J W; Bellini, F; Bersani, A; Biassoni, M; et al.
Abstract: The CUORE-0 experiment searched for neutrinoless double beta decay in 130 Te using an array of 52 tellurium dioxide crystals, operated as bolometers at a temperature of 10 mK. It took data in the Gran Sasso National Laboratory (Italy) since March 2013 to March 2015. We present the results of a search for neutrinoless double beta decay in 9.8 kg-years 130 Te exposure that allowed us to set the most stringent limit to date on this half-life. The performance of the detector in terms of background and energy resolution is also reported.